PENGGUNAAN BAHASA INGGRIS BAGI PRAMUWISATA SEBAGAI MEDIA KOMUNIKASI DALAM MENJELASKAN RELIEF KEPADA WISATA ASING DI CANDI PRAMBANAN - Yanuar, Beta Rifki; Puspitasari, indah (Jurnal Vokasia, 2021)
The purposes of this study were to find out how to guide foreign tourist in Prambanan Temple, the technique that must be used to guide, the obstacles faced by guides when guiding foreign tourists and to find out the solutions to deal with that obstacle.The author used several methods such as observation, interview, documentation and literature. Giving information in English were divided into two categories, those are direct and indirect method. There are several steps in practice of providing information in English such as giving a smile and greeting, offering assistance, giving information about Prambanan relief, saying goodbye and asking tourists to give some critics and suggestions.There were obstacles when the guides gave information to tourists such as, experiencing nervousness when guiding, lack of information boards in each temple and relief, and lack of mastery of the material. However, there are solutions to overcome these obstacles, such as conducting a briefing before guiding activities, making information boards, conducting routine evaluations and determining the standardization of knowledge forvisitors